2016
DOI: 10.2215/cjn.05000516
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Change Disease

Abstract: Minimal change disease (MCD) is a major cause of idiopathic nephrotic syndrome (NS), characterized by intense proteinuria leading to edema and intravascular volume depletion. In adults, it accounts for approximately 15% of patients with idiopathic NS, reaching a much higher percentage at younger ages, up to 70%-90% in children >1 year of age. In the pediatric setting, a renal biopsy is usually not performed if presentation is typical and the patient responds to therapy with oral prednisone at conventional dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
383
1
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(426 citation statements)
references
References 82 publications
8
383
1
21
Order By: Relevance
“…Reporter bias may account for this lack of difference, however, as adverse events were prospectively surveyed among the short-term treated patients and extracted from registry records in the historical, conventionally treated cohort patients. For example, whereas most studies in the literature report a rate of infection between 5 and 15% in adults with MCD on corticosteroids [1][2][3], only 6 of the 140 (4.3%) adult MCD patients in the longterm steroid group had such complications. Despite no statistically significant adverse event differences between the short-and long-term steroid groups, some clear trends have emerged including a lower incidence of infectious-related hospitalization, peptic ulcer disease, and femoral head osteonecrosis.…”
Section: Doi: 101159/000495351mentioning
confidence: 97%
See 1 more Smart Citation
“…Reporter bias may account for this lack of difference, however, as adverse events were prospectively surveyed among the short-term treated patients and extracted from registry records in the historical, conventionally treated cohort patients. For example, whereas most studies in the literature report a rate of infection between 5 and 15% in adults with MCD on corticosteroids [1][2][3], only 6 of the 140 (4.3%) adult MCD patients in the longterm steroid group had such complications. Despite no statistically significant adverse event differences between the short-and long-term steroid groups, some clear trends have emerged including a lower incidence of infectious-related hospitalization, peptic ulcer disease, and femoral head osteonecrosis.…”
Section: Doi: 101159/000495351mentioning
confidence: 97%
“…Patients frequently experience adverse effects of corticosteroid therapy, and a high rate of relapse further plagues the clinical course of MCD across all age spectrums, often necessitating repeat exposure to steroids and/or other, potentially toxic immunosuppressive agents [2]. Therefore, since the initial recognition that corticosteroids led to a remission of "nil disease," nephrologists have consistently sought the answer to a relatively straightforward question for MCD: What is the least amount of corticosteroids my patient needs to achieve a remission and not relapse immediately?The answer to that question has been worked out for the pediatric MCD population over a span of more than 5 decades, and the current standard of care is a regimen of daily corticosteroids (e.g., prednisone 60 mg/m 2 ) for 4 weeks followed by an additional 4-8 weeks of alternate day corticosteroids (e.g., prednisone 40 mg/m 2 ) [3]. A number of clinical trials and a meta-analysis of these trials have found no additional benefit for children with MCD in extending corticosteroid exposure past the 2-or 3-month mark [4][5][6][7].…”
mentioning
confidence: 99%
“…Nevertheless, frequent relapsers and steroid-dependent patients may develop signs of glucocorticoid toxicity and will require different therapies. Glucocorticoid-sparing strategies include a course of 2-3 months of cyclophosphamide, levamisole, mycophenolate (18), cyclosporine (19), or rituximab (20).…”
Section: Indications For Glucocorticoids In Gn Minimal Change Diseasementioning
confidence: 99%
“…Minimal change disease (MCD), also called lipid nephrosis, is a common type of primary glomerular diseases and one of the most common reasons for nephrotic syndrome [1]. MCD accounts for 70–90% of nephrotic syndrome in children and approximately 15% in adults [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…MCD accounts for 70–90% of nephrotic syndrome in children and approximately 15% in adults [1, 2]. MCD is mainly characterized by proteinuria due to the damage of podocytes [3].…”
Section: Introductionmentioning
confidence: 99%